COMPARATIVE STUDY OF STANDARD VERSUS LOW-PRESSURE PNEUMOPERITONEUM IN REDUCING POSTOPERATIVE COMPLICATIONS FOLLOWING LAPAROSCOPIC CHOLECYSTECTOMY - ISMAIL , T; FAROOQI , HA; KHAN , DA; IQBAL , M; HASSAN , R; AHMED , A (Biological and Clinical Sciences Research Journal, 2024)
Laparoscopic cholecystectomy is a widely used technique for managing gallstone disease, with pneumoperitoneum playing a critical role in procedural success and associated postoperative outcomes. However, conflicting evidence exists regarding the efficacy of standard versus low-pressure pneumoperitoneum in minimizing postoperative pain and nausea. Objective: To compare postoperative pain and nausea in patients undergoing laparoscopic cholecystectomy using standard pressure (12-15 mmHg) versus low-pressure (8-11 mmHg) pneumoperitoneum. Methods: A randomized controlled trial was conducted at the Department of Surgery, Benazir Bhutto Hospital, Rawalpindi. A total of 100 patients were randomly assigned to either the standard pressure (n=50) or low-pressure (n=50) pneumoperitoneum groups. Pain levels were measured using a Visual Analog Scale (VAS) at 0, 6, 12, and 24 hours post-surgery, while nausea frequency was assessed at corresponding intervals. Results: Patients in the low-pressure group experienced significantly reduced postoperative pain at 6, 12, and 24 hours (p<0.05) and lower rates of nausea at all time points assessed (p<0.05) compared to the standard pressure group. Conclusion: Low-pressure pneumoperitoneum significantly reduces postoperative pain and nausea, suggesting it may be preferable for patients undergoing laparoscopic cholecystectomy. Further research is needed to explore its long-term impact on recovery and potential complications.